The First Photo-Record of the Amur Falcon in Kazakhstan - Kordian Bartoszuk; Elvira G. Nikolenko; Igor V. Karyakin (Пернатые хищники и их охрана)
This short report provides information about the first reliable meeting of the Amur Falcon (Falco amurensis) in Kazakhstan in the modern period.